Delusional Infestation: Perspectives from Scottish Dermatologists and a 10-year Case Series from a Single Centre - Yee Ling Wong; Andrew Affleck; Alexander M. Stewart (Medical Journals Sweden, 2018)
Perceptions of the clinical management of delusional infestation (DI) were compared with clinical outcomes in this 10-year case series from a single centre in Dundee, UK. An online questionnaire (survey-monkey, a TM brand of online survey available for free for basic use) was sent to Scottish Dermatologists to gauge their opinions and confidence in the management of DI. Also, a retrospective review of medical case notes of patients seen by dermatologists in one institution was undertaken and clinical outcomes were reported by patients' general practitioners (GP). The survey showed that 61% of responding dermatologists encountered 1-5 cases of DI per year. Twenty-four percent respondees were 'confident' in managing patients with DI, 54% were 'somewhat confident'. Forty-seven patients (62% female, 70% single) were seen over the 10 years; 43% brought a self-collected specimen to clinic, 68% of patients had a psychiatric comorbidity, 23% of patients had primary DI and 11/47 (23%) were seen by a psychiatrist. Clinical outcomes as rated by patients' GPs were reasonable or good in 2/3 patients. A poor outcome was seen in 12 patients and associated with chronic pain in 50% (p< 0.01) and psychiatric comorbidity in 100% (p < 0.01). We conclude that good outcomes can be achieved in some patients with DI without psychiatric input and without psychoactive treatment.